Analytical Studies of Vanadiferrous and Titaniferrous Magnetites of Dublabera Area of Singhbhum - Kamal, K.P.; Mujtaba, S.G.; Trehan, A.K. (Asian Journal of Chemistry, 2010)
In the present work the analytical studies of vanadiferrous and titaniferrous magnetities are performed.